IMPACT OF THE INCREASING CATCHABILITY COEFFICIENT OF THE LARGE PURSE SEINER TO THE DEPLETION OF THE SMALL PELAGIC FISH BIOMASS IN THE JAVA SEA - Suherman Banon Atmaja; Duto Nugroho (Research Center for Fisheries, 2011)
Understanding the dynamics of marine fish resources and its ecosystems requires long term historical data from a particular fisheries in a certain area.